A method to determine radial speed of target from the FMCW radar signal - Sediono, Wahju; Lestari, Andrian Andaya (2008)
An established method to detect a target from the FMCW radar signal is implemented by using the method of range FFT (Fast Fourier Transform). By repeating the same procedure many times at a certain azimuth angle, it is possible to additionally compute the radial speed of the suspected target. This paper describes a method to determine the radial speed of target by extracting the phase data from the repeated range FFTs. To verify this method a series of computer simulations was conducted at our research group.